Assessment of a Pedestrian Bridge Dynamics Using Interferometric Radar System IBIS-FS. (2017) - Sofi, M.; Lumantarna, E.; Mendis, P.A.; Duffield, C.; Rajabifard, A.
Abstract: Traffic loads are increasing, trucks are getting larger and heavier and this is a trend expected to continue. This may cause an increase in the rate of a bridge structural deterioration. As such there needs to be innovative methods of assessing bridge structural health for an improved structural asset management. IBIS-FS is a new piece of equipment based on interferometric radar developed recently for the purpose of structural health assessment and monitoring. It is presented as offering unique advantages over conventional monitoring solutions such as its portability and that it does not require direct contact with the structure. This study explores the use of IBIS-FS to detect changes in a pedestrian bridge natural frequencies over time from which a change in bridge stiffness, and subsequently, the level of structural deterioration, can be obtained. In particular, the focus of this study centers on validating the natural frequencies obtained from the interferometric measurements with those determined from more conventional methods. It was found that IBIS is capable of capturing the natural frequencies of the bridge investigated demonstrating its potential use in the structural health monitoring of bridges.